Behavioral Economics Strategies to Improve Medication Adherence in Diabetes - Qiao , Haobo (Transactions on Economics, Business and Management Research, 2024)
Nowadays, diabetes has become an international challenge. In spite of the great technological advances in human society compared to a few decades ago, a cure for this disease has never been discovered. Hundreds of millions of patients are suffering from it, and in order to enable diabetics to keep their condition as stable as possible, this paper examines how to enhance patients' medication adherence from the perspective of behavioral economics. After reclassification of the influencing factors through tables such as pivot tables, among the data of 1127 patients selected who required long-term medication, 559 were affected by Convergence and Avoidance of Harm and were reluctant to take medication. Another 231 participants suffered from cognitive bias. A further 165 patients made irrational calculations about whether or not to take their medication. The remaining patients were influenced by some objective factors. Based on the analysis of the distinct causes of medication non-adherence in diabetic patients, it was found that this could be tackled by allowing patients to be more informed about their condition, improving access to education in order to break down information barriers, increasing the presence of family and friends, and illustrating the cost of treatment with the help of visualization tools. Beyond financial and dietary approaches, these facilitation methods could nudge as much to stabilize patients' medication-taking behaviors.